In vitro investigation of the molecular relationship between mitochondrial dysfunction and neurogenesis in autism aetiology - Van Der Watt, Mignon (Department of Molecular and Cell Biology, 2024)
Mitochondrial function is integral in the regulation of neurogenesis. Our research group previously reported differentially methylated genes and metabolomic evidence converging on mitochondrial dysfunction in a South African autism spectrum disorder (ASD) cohort. Thus, subtle mitochondrial dysfunction is hypothesized to contribute to the pathogenesis of a subset of ASD by altering early neurogenesis. Given the inaccessibility of the developing brain, cell culture model systems are needed to investigate the molecular relationship between mitochondrial dysfunction and neuronal differentiation as it pertains to ASD aetiology. A key differentially methylated gene was Propionyl-CoA Carboxylase Subunit B (PCCB), a mitochondrial enzyme involved in metabolizing short fatty acids like propionic acid (PPA). Disruption of PCCB function could result in toxic accumulation of PPA. Furthermore, PPA is used to induce mitochondrial dysfunction in in vitro models and recapitulate ASD-like behaviours in animal models. Thus, PPA treatments can be used to model the effect of PCCB disruption to investigate molecular links between ASD-associated mitochondrial dysfunction and neurogenesis in vitro. The aims of this thesis were to i) induce and characterise mitochondrial dysfunction in the SH SY5Y cell culture model, ii) investigate the temporal cellular responses to PPA-induced mitochondrial stress, iii) confirm and characterise successful neuronal differentiation of SH SY5Y cells induced by a de novo differentiation protocol, and iv) investigate the effects of PPA exposure on morphological and biochemical changes seen during neuronal differentiation of the SH-SY5Y cell line. Undifferentiated neuron-like SH-SY5Y cells were treated with PPA concentrations ranging from 0-10mM PPA to induce mitochondrial stress. Cell viability and cytotoxicity under the range of PPA concentrations were examined using MTT assays to determine dosages of PPA which induced mitochondrial stress. The expression of mitochondrial homeostasis (mitostasis) genes previously associated with ASD were measured in response to PPA exposure. Reverse transcription quantitative polymerase chain reaction (RT-qPCRs) of mitochondrial biogenesis (mitogenesis) (C-MYC, PGC-α, NRF1, NFE2L2, TFAM) and mitochondrial fusion (STOML2, OPA1) genes were performed to identify PPA-responsive genes and to get initial insights on the effect of PPA treatments on transcriptional regulation of mitostasis. Mitochondrial membrane potential (DYm) was measured in response to acute PPA stress using TMRE (Tetramethylrhodamine, ethyl ester) assays. Additionally, RT-qPCRs were used to measure the temporal expression of C-MYC and PGC-1α, two integral factors in regulating interactions between mitochondrial function and neurogenesis, in response to chronic PPA exposure. Differentiation of SH-SY5Y cells was induced using retinoic acid and brain-derived neurotrophic factor. Successful neuronal differentiation was morphologically quantified using phase-contrast microscopy and the ‘Neuron J’ plugin in Image J. Neuronal differentiation was also biochemically confirmed using immunocytochemistry for the 5 immature neuron marker, Nestin, in comparison to the mature neuron marker, Beta-III tubulin. The same phase-contrast microscopy and immunocytochemistry measurements were used to determine the effect of 5mM PPA treatments on the process of neuronal differentiation. PPA was found to induce mitochondrial stress in SH-SY5Y cells by the dose-dependent decreases in cell viability and DYm. Furthermore, PPA disrupted the transcriptional regulation of mitostasis, mitogenesis, and mitochondrial fusion. Dose-dependent decreases in mRNA expression were observed for NRF1, NFE2L2, TFAM, STOML2, and C-MYC. Additionally, PPA disrupted the dynamic regulatory crosstalk between mitochondrial function and neurogenesis as highlighted by temporal attenuation of C-MYC and the multi-directional expression of PGC-1α. The de novo neuronal differentiation protocol induced increased neurite elongation and branching, cell cycle withdrawal, and upregulated Beta-III tubulin expression which indicates successful SH-SY5Y differentiation. However, PPA exposure altered neuronal differentiation. PPA treatment resulted in decreased neurite elongation and branching along with altered expression and localization of the neuronal markers. This study establishes a reductionist ex vivo cell culture model system to study neurodevelopment in vitro. Furthermore, the application of this model provides insights into the molecular relationship between ASD-associated mitochondrial dysfunction and neurogenesis. ASD-associated mitochondrial dysfunction results in disrupted transcriptional regulation of mitostasis. This transcriptional dysregulation has implications on the rate and nature of neuronal differentiation and maturation. Although this research provides initial insights into the molecular mechanisms between ASD-associated mitochondrial dysfunction and neurogenesis, there is a need for further research to gain greater understanding of this molecular relationship and its outcomes.